A Decade of Rainfall Manipulation Reveals Growing‐Season Aridity as a Key Determinant of Grassland Productivity and Stability - Sally A. Power; Manjunatha H. Chandregowda; Kirk Barnett; Juan Pineiro; Shun Hasegawa; Coline Deveautour; Eleanor Gibson‐Forty; Jeff Chieppa; Scott N. Johnson; Sarah Facey; Raul Ochoa‐Hueso (Global Change Biology, 2026)
Warming‐driven intensification of the hydrological cycle is altering global rainfall patterns. However, the relative importance of changes in the amount versus timing of rainfall and the role of atmospheric drivers of moisture demand in modifying relationships between rainfall, biodiversity and ecosystem functioning are currently unresolved. To address this, we undertook a 10‐year rainfall manipulation experiment in a mesic grassland in New South Wales, Australia. We used rain shelters to achieve five rainfall treatments: (i) ambient, (ii) ambient +50% (IA), (iii) ambient −50% (RA), (iv) reduced frequency (RF, cumulative ambient rainfall applied once every 3 weeks) and (v) summer drought (SD, no rain during the Austral summer). We found that inter‐annual variation in ANPP was best explained by the amount of growing season rainfall relative to potential evapotranspiration (i.e., P/PET, or aridity) (R 2 adj 0.52). Reductions in the amount of rainfall, particularly during summer, were associated with productivity decline, shifts in community composition and a loss of diversity. However, reducing the frequency of rain events had no overall effect on productivity, despite a loss of species diversity. Notably, treatment‐related declines in diversity and/or richness were associated with both increases (IA) and decreases (SD) in temporal stability of ANPP and the stabilising role of species asynchrony, thereby highlighting the importance of species identity and associated functional traits for community stability. Our study uniquely emphasises the importance of accounting for seasonal drivers of moisture demand when predicting functional responses to changes in rainfall regimes and highlights how the ecological mechanisms underpinning community stability are influenced by changes in both the amount and timing of rainfall. These mechanistic insights can enhance the predictive capacity of Earth system models and inform targeted management strategies to offset the negative effects of future, more extreme rainfall on the ecosystem services provided by global grasslands.

Nutrient Enrichment Increases Grassland Biomass Sensitivity to Interannual Precipitation Variation - Ingrid J. Slette; Eric W. Seabloom; Carlos Alberto Arnillas; Jonathan D. Bakker; Dana Blumenthal; Jane A. Catford; Scott L. Collins; Nico Eisenhauer; Philip A. Fay; Magda Garbowski; Sylvia Haider; W. Stanley Harpole; et al. (Global Change Biology, 2026)
Primary production underpins much of ecosystem functioning and is often limited by nutrient and water availability. Ongoing global increases in nutrient inputs and interannual precipitation variability are thus likely to impact primary production, with unclear consequences for interannual variability in plant biomass. We used data from 35 grasslands in the Nutrient Network coordinated fertilization experiment to test if nutrient addition alters the response of plant biomass to year‐to‐year variation in growing season precipitation, and whether the effects of nutrient addition vary with factors such as site aridity or plant community composition. Nutrient addition increased biomass (by an average of 46% across sites), rain‐use efficiency (by 48%), and the sensitivity of biomass to interannual variation in precipitation (i.e., larger increase in biomass in wet years; by 13%), but did not change the strength of the interannual precipitation‐biomass correlation. Both sensitivity and correlation strength were higher in more arid sites, regardless of nutrient addition. These results suggest that grassland ecosystem functioning may become more variable from year to year as nutrient enrichment increases biomass sensitivity to precipitation and precipitation becomes more variable.

Exploring the impact of climate model accuracy and baseline conditions on estimates of future climate change - Scott B. Power (Theoretical and Applied Climatology, 2026)
Climate change projections depend on future climatic conditions and a historical reference period. A key uncertainty in estimating precipitation projections stems from the uncertain net contribution of internal variability to the value of precipitation averaged over the reference period, $$\:δ_{1}$$ . Here we derive equations that, when used with observational data, climate model output, and Bayes’ Theorem, can estimate this contribution. The resulting estimate depends on how accurately the ensemble mean is assumed to simulate externally forced change (EFC). Solutions are obtained for cases where the ensemble mean is perfectly accurate, and where it under- or overestimates EFC. The method is applied in a Case Study on precipitation change in south-east Australia. If the ensemble accurately simulates EFC from 1900–1999 to 2000–2021 then the CMIP5-based estimate of $$\:δ_{1}$$ has a mean of -31.2 mm, which is -8.1% of the 2000–2021 multi-model mean precipitation. As this value is larger in magnitude than the projected drying over the entire 21st century under the RCP4.5 scenario, precipitation will most likely increase relative to 2000–2021, if the EFC is accurately simulated. This contrasts sharply with widespread expectations. The expected change in precipitation relative to 2000–2021 remains positive through to the mid-21st century even if the ensemble mean EFC is inaccurate, provided that the magnitude of the simulated EFC exceeds 50% of its real-world counterpart. These results have significant implications for people who produce, communicate or use projections. Constraining $$\:δ_{1}$$ impacts estimates of future change via a process called “ reversion to the mean ”.

Statistical properties of multi-year droughts in climate models and observations with corresponding theoretical estimates - Scott B. Power; Zoe E. Gillett (Climate Dynamics, 2025)
Multi-year droughts (MYDs) can have major impacts on ecosystems, agriculture, water resources, economies, people and societies. Here, we examine statistical properties of MYDs consisting of uninterrupted sequences of years in which annual precipitation falls below a given threshold. We examine statistics including the proportion of years that are part of droughts of duration $$\ge n$$ ≥ n years, the proportion of droughts that have duration $$\ge n$$ ≥ n years, and both the duration and the number of droughts with duration $$\ge n$$ ≥ n years, in thirty-eight 200-year-long simulations of CMIP6 coupled global climate models under pre-industrial control conditions. We also derive formulae that approximate the average value of these and other statistics using simple stochastic models. The theoretical values obtained agree reasonably well with their Multi-Model Mean (MMM) climate model counterparts over the globe. Regional contrasts in the value of the statistics for MYDs consisting of uninterrupted sequences of years with below-average precipitation can be largely explained by spatial variations in the percentile of the mean. Corresponding formulae that account for non-zero temporal autocorrelation tend to agree somewhat more closely with the MMM values. MYD statistics are estimated using observational data and compared with theoretical and climate model estimates. The formulae incorporating non-zero autocorrelation provide a better estimate of the observational values than do MMM values or formulae derived assuming zero autocorrelation.

From field station to forecast: managing data at the Alaska Volcano Observatory - Michelle L. Coombs; Cheryl E. Cameron; Hannah R. Dietterich; Eleanor S. Boyce; Aaron G. Wech; Ronni Grapenthin; Kristi L. Wallace; Tom Parker; Taryn Lopez; Scott Crass; David Fee; Matthew M. Haney; et al. (Bulletin of Volcanology, 2024)

Corrigendum to “Impacts of environmental feedbacks on the production of a Central Queensland beef enterprise in a future climate” [Agricultural Systems 214 (2024) 1–13/103838] - Duc-Anh An-Vo; David Cobon; Jyoteshna Owens; Adam Liedloff; Tim Cowan; Scott Power (Agricultural Systems, 2024)

Statistical relationships between the Interdecadal Pacific Oscillation and El Niño–Southern Oscillation - Hanna Heidemann; Tim Cowan; Scott B. Power; Benjamin J. Henley (Climate Dynamics, 2024)
The climate of the Pacific Ocean varies on interannual, decadal, and longer timescales. This variability is dominated by the El Niño–Southern Oscillation (ENSO) and the Interdecadal Pacific Oscillation (IPO), both of which have profound impacts on countries within and well beyond the Pacific. To date, previous studies have only examined a small subset of the possible links between ENSO, its diversity, and the IPO. Here we focus on the statistical relationship between decadal variability in ENSO properties and the IPO, testing the null hypothesis that the IPO arises from random decadal changes in ENSO activity, including ENSO diversity. We use observed sea surface temperature (SST) records since 1920 to investigate how the timing, structure, frequency, duration, and magnitude of El Niño and La Niña events differ between IPO phases. We find that using the relative frequency of El Niño and La Niña events and either the mean event duration or SST magnitude can reproduce up to 60% of the IPO Tripole Index timeseries. While the spatial SST patterns that represent the IPO and ENSO are similar, the IPO is meridionally broader in the central to eastern Pacific, which may be caused by a lagged relationship with low-frequency SST variability in the equatorial Pacific. In addition, North Pacific SST anomalies of opposite sign to the tropical Pacific SST anomalies is a unique feature of the IPO that cannot be explained by decadal ENSO variability. This suggests a clear IPO and ENSO relationship, but also independence in some of the IPO’s characteristics.

Impacts of environmental feedbacks on the production of a Central Queensland beef enterprise in a future climate - Duc-Anh An-Vo; David Cobon; Jo Owens; Adam Liedloff; Tim Cowan; Scott Power (Agricultural Systems, 2024)

Past and future rainfall change in sub-regions of Victoria, Australia - Surendra P. Rauniyar; Scott B. Power (Climatic Change, 2023)
We examine rainfall variability and change in three sub-regions of the state of Victoria in Australia: the Murray Basin Victoria (MBVic), southeast Victoria (SEVic), and southwest Victoria (SWVic). These sub-regions represent three different hydrological super-catchments over Victoria and received average cool season rainfall for the 1997–2018 period, about 15%, 11%, and 8% less, respectively, than the 1900–1959 average. All three observed declines are shown to be very unusual in terms of historical variability. On analysing CMIP5 models under different forcing conditions (preindustrial, historical-all, historical-GHGs-only, historical-natural-only, RCP2.6, RCP4.5, and RCP8.5), we estimate that external forcing caused 30% of the observed drying in SWVic, 18% in MBVic, and 17% in SEVic. The external forcing contributions to the observed trend for the 1900–2018 period are estimated to be 56%, 17%, and 24% for SWVic, MBVic, and SEVic, respectively. Taken at face value, these figures suggest that only the 1900–2018 trend in SWVic was dominated by external forcing. Nearly all models underestimate the magnitude of the observed drying. This arises because models underestimate the magnitude of decadal variability, and because models might also underestimate externally forced drying, and/or the contribution of internal variability in the real world to the observed event was unusually large. By 2037, approximately 90% of the models simulate drying in SWVic, even under a low emissions scenario. Under a high emission scenario, the anthropogenically forced drying towards the late twenty-first century is so large in all three sub-regions that internal variability appears too small to offset it.

Climate processes and drivers in the Pacific and global warming: a review for informing Pacific planning agencies - Savin Chand; Scott Power; Kevin Walsh; Neil Holbrook; Kathleen McInnes; Kevin Tory; Hamish Ramsay; Ron Hoeke; Anthony S. Kiem (Climatic Change, 2023)
Pacific Island countries are vulnerable to climate variability and change. Developing strategies for adaptation and planning processes in the Pacific requires new knowledge and updated information on climate science. In this paper, we review key climatic processes and drivers that operate in the Pacific, how they may change in the future and what the impact of these changes might be. In particular, our emphasis is on the two major atmospheric circulation patterns, namely the Hadley and Walker circulations. We also examine climatic features such as the South Pacific Convergence Zone and Intertropical Convergence Zone, as well as factors that modulate natural climate variability on different timescales. It is anticipated that our review of the main climate processes and drivers that operate in the Pacific, as well as how these processes and drivers are likely to change in the future under anthropogenic global warming, can help relevant national agencies (such as Meteorological Services and National Disaster Management Offices) clearly communicate new information to sector-specific stakeholders and the wider community through awareness raising.

Estimating future rainfall distributions in a changing climate for water resource planning: Victoria, Australia - Surendra P. Rauniyar; Scott B. Power (Climate Dynamics, 2023)
Here we use observations and simulations from 40 global climate models from phase 5 of the Coupled Model Intercomparison Project (CMIP5), under preindustrial, historical, and a high emission scenario (RCP8.5) to provide estimates of Victorian cool season (April–October) rainfall for the coming century. This includes a new method which exploits recent research that estimated the relative contribution of external forcing and natural variability to the observed multidecadal decline in cool season rainfall in Victoria from 1997. The new method is aimed at removing the influence of external forcing on Victoria’s cool-season rainfall, effectively rendering a stationary time-series. The resulting historical record is then modified by scaling derived from the mean projected change evident in climate models out to 2100. The results suggest that the median value of the All-Victoria rainfall PDF will decrease monotonically over the remainder of the twenty-first century under RCP8.5. The likelihood that All-Victoria rainfall in any given year from 2025 onward will be below the observed 5th percentile of the observations (291 mm) increases monotonically, becoming three times larger by the end of the century. The new method is assessed using cross-validation and its ability to hindcast observed multidecadal rainfall change. The latter indicates that CMIP5 models poorly replicate recent interdecadal rainfall change. So, while we have more confidence in the new method because it accounts for the non-stationarity in the observed climate, limitations in the CMIP5 models results in us having low confidence in the reliability of the estimated future rainfall distributions.

Two canonically aerobic foraminifera express distinct peroxisomal and mitochondrial metabolisms - Christopher Powers; Fatma Gomaa; Elizabeth B. Billings; Daniel R. Utter; David J. Beaudoin; Virginia P. Edgcomb; Colleen M. Hansel; Scott D. Wankel; Helena L. Filipsson; Ying Zhang; Joan M. Bernhard (Frontiers in Marine Science, 2022)
Certain benthic foraminifera thrive in marine sediments with low or undetectable oxygen. Potential survival avenues used by these supposedly aerobic protists include fermentation and anaerobic respiration, although details on their adaptive mechanisms remain elusive. To better understand the metabolic versatility of foraminifera, we studied two benthic species that thrive in oxygen-depleted marine sediments. Here we detail, via transcriptomics and metatranscriptomics, differential gene expression of Nonionella stella and Bolivina argentea , collected from Santa Barbara Basin, California, USA, in response to varied oxygenation and chemical amendments. Organelle-specific metabolic reconstructions revealed these two species utilize adaptable mitochondrial and peroxisomal metabolism. N. stella , most abundant in anoxia and characterized by lack of food vacuoles and abundance of intracellular lipid droplets, was predicted to couple the putative peroxisomal beta-oxidation and glyoxylate cycle with a versatile electron transport system and a partial TCA cycle. In contrast, B. argentea , most abundant in hypoxia and contains food vacuoles, was predicted to utilize the putative peroxisomal gluconeogenesis and a full TCA cycle but lacks the expression of key beta-oxidation and glyoxylate cycle genes. These metabolic adaptations likely confer ecological success while encountering deoxygenation and expand our understanding of metabolic modifications and interactions between mitochondria and peroxisomes in protists.

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

SGLT2 inhibition attenuates arterial dysfunction and decreases vascular F-actin content and expression of proteins associated with oxidative stress in aged mice - Rogerio N. Soares; Francisco I. Ramirez-Perez; Francisco J. Cabral-Amador; Mariana Morales-Quinones; Christopher A. Foote; Thaysa Ghiarone; Neekun Sharma; Gavin Power; James A. Smith; R. Scott Rector; Luis A. Martinez-Lemus; Jaume Padilla; et al. (GeroScience, 2022)
Aging of the vasculature is characterized by endothelial dysfunction and arterial stiffening, two key events in the pathogenesis of cardiovascular disease (CVD). Treatment with sodium glucose transporter 2 (SGLT2) inhibitors is now known to decrease cardiovascular morbidity and mortality in type 2 diabetes. However, whether SGLT2 inhibition attenuates vascular aging is unknown. We first confirmed in a cohort of adult subjects that aging is associated with impaired endothelial function and increased arterial stiffness and that these two variables are inversely correlated. Next, we investigated whether SGLT2 inhibition with empagliflozin (Empa) ameliorates endothelial dysfunction and reduces arterial stiffness in aged mice with confirmed vascular dysfunction. Specifically, we assessed mesenteric artery endothelial function and stiffness (via flow-mediated dilation and pressure myography mechanical responses, respectively) and aortic stiffness (in vivo via pulse wave velocity and ex vivo via atomic force microscopy) in Empa-treated (14 mg/kg/day for 6 weeks) and control 80-week-old C57BL/6 J male mice. We report that Empa-treated mice exhibited improved mesenteric endothelial function compared with control, in parallel with reduced mesenteric artery and aortic stiffness. Additionally, Empa-treated mice had greater vascular endothelial nitric oxide synthase activation, lower phosphorylated cofilin, and filamentous actin content, with downregulation of pathways involved in production of reactive oxygen species. Our findings demonstrate that Empa improves endothelial function and reduces arterial stiffness in a preclinical model of aging, making SGLT2 inhibition a potential therapeutic alternative to reduce the progression of CVD in older individuals. Graphical abstract

Effects of short-term decomposition on isotope values of fish tissues under natural conditions - Kathryn S. Peiman; Hsien-Yung Lin; Michael Power; Scott G. Hinch; David A. Patterson; Steven J. Cooke (Aquatic Ecology, 2022)

The 16th Workshop on Antarctic Meteorology and Climate and 6th Year of Polar Prediction in the Southern Hemisphere Meeting - David H. Bromwich; Matthew A. Lazzara; Arthur M. Cayette; Jordan G. Powers; Kirstin Werner; John J. Cassano; Steven R. Colwell; Scott Carpentier; Xun Zou (Advances in Atmospheric Sciences, 2022)

Microbial processing of plant remains is co‐limited by multiple nutrients in global grasslands - Raúl Ochoa‐Hueso; Elizabeth T. Borer; Eric W. Seabloom; Sarah E. Hobbie; Anita C. Risch; Scott L. Collins; Juan Alberti; Héctor A. Bahamonde; Cynthia S. Brown; Maria C. Caldeira; Pedro Daleo; Chris R. Dickman; et al. (Global Change Biology, 2020)
Microbial processing of aggregate‐unprotected organic matter inputs is key for soil fertility, long‐term ecosystem carbon and nutrient sequestration and sustainable agriculture. We investigated the effects of adding multiple nutrients (nitrogen, phosphorus and potassium plus nine essential macro‐ and micro‐nutrients) on decomposition and biochemical transformation of standard plant materials buried in 21 grasslands from four continents. Addition of multiple nutrients weakly but consistently increased decomposition and biochemical transformation of plant remains during the peak‐season, concurrent with changes in microbial exoenzymatic activity. Higher mean annual precipitation and lower mean annual temperature were the main climatic drivers of higher decomposition rates, while biochemical transformation of plant remains was negatively related to temperature of the wettest quarter. Nutrients enhanced decomposition most at cool, high rainfall sites, indicating that in a warmer and drier future fertilized grassland soils will have an even more limited potential for microbial processing of plant remains.

The impact of global warming and the El Niño-Southern Oscillation on seasonal precipitation extremes in Australia - François P. D. Delage; Scott B. Power (Climate Dynamics, 2020)
The El Niño-Southern Oscillation (ENSO) drives substantial variability in precipitation and drought risk over Australia. Understanding the combined effect of anthropogenic forcing and ENSO on Australian precipitation extremes over the coming century can assist adaptation efforts. Here we use 24 CMIP5 climate models to examine externally forced changes in the frequency of “droughts”, when precipitation falls below the pre-industrial Decile 1 threshold. We focus on June to November (i.e., southern hemisphere Winter–Spring season) because precipitation during this period is important for agricultural production and recharging reservoirs in many parts of the country. The analysis in this paper is based on two 90-year simulations (1900–1989 and 2010–2099) for Historical and RCP8.5 scenarios. We show that the frequency of droughts, including droughts occurring in consecutive Winter–Spring seasons, is projected to increase in the twenty-first century under the RCP8.5 scenario in all eight Natural Resource Management (NRM) “clusters”. Approximately 60% of years are projected to be drought years in Perth, 35% in Adelaide, 30% in Melbourne, and approximately 20–25% of years in Sydney, Canberra and Brisbane. The relative frequency distributions of seasonally averaged Winter–Spring precipitation shift to lower values in all NRM clusters. However, apart from the Southern and Southwestern Flatlands, the shifts are accompanied by changes in the shape of the distributions whereby the high end of the distributions do not shift as much as other parts of the distribution and the wettest seasons become marginally wetter. This means that in most locations generally drier conditions are projected to be infrequently punctuated by seasons that are just as wet or wetter than the wettest years experienced during the twentieth century. While the models generally do a poor job in simulating ENSO precipitation teleconnections over Australia, an increase in ENSO-driven variability is suggested for the Wet Tropics, the Monsoonal North, the Central Slopes and the Southern and Southwestern Flatlands.

The 13th and 14th Workshops on Antarctic Meteorology and Climate - Matthew A. Lazzara; Sophie A. Orendorf; Taylor P. Norton; Jordan G. Powers; David H. Bromwich; Scott Carpentier; John J. Cassano; Steven R. Colwell; Arthur M. Cayette; Kirstin Werner (Advances in Atmospheric Sciences, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Endurance exercise protects skeletal muscle against both doxorubicin-induced and inactivity-induced muscle wasting - Scott K. Powers; Jose A. Duarte; Branden Le Nguyen; Hayden Hyatt (Pflügers Archiv - European Journal of Physiology, 2019)

Drought negates growth stimulation due to root herbivory in pasture grasses - Kirk L. Barnett; Scott N. Johnson; Sally A. Power (Oecologia, 2018)

What can decadal variability tell us about climate feedbacks and sensitivity? - Robert Colman; Scott B. Power (Climate Dynamics, 2018)

The 12th Workshop on Antarctic Meteorology and Climate - Matthew A. Lazzara; Jordan G. Powers; Carol A. Costanza; David H. Bromwich; Scott Carpentier; Steve R. Colwell (Advances in Atmospheric Sciences, 2018)

Drought consistently alters the composition of soil fungal and bacterial communities in grasslands from two continents - Raúl Ochoa‐Hueso; Scott L. Collins; Manuel Delgado‐Baquerizo; Kelly Hamonts; William T. Pockman; Robert L. Sinsabaugh; Melinda D. Smith; Alan K. Knapp; Sally A. Power (Global Change Biology, 2018)
The effects of short‐term drought on soil microbial communities remain largely unexplored, particularly at large scales and under field conditions. We used seven experimental sites from two continents (North America and Australia) to evaluate the impacts of imposed extreme drought on the abundance, community composition, richness, and function of soil bacterial and fungal communities. The sites encompassed different grassland ecosystems spanning a wide range of climatic and soil properties. Drought significantly altered the community composition of soil bacteria and, to a lesser extent, fungi in grasslands from two continents. The magnitude of the fungal community change was directly proportional to the precipitation gradient. This greater fungal sensitivity to drought at more mesic sites contrasts with the generally observed pattern of greater drought sensitivity of plant communities in more arid grasslands, suggesting that plant and microbial communities may respond differently along precipitation gradients. Actinobateria, and Chloroflexi, bacterial phyla typically dominant in dry environments, increased their relative abundance in response to drought, whereas Glomeromycetes, a fungal class regarded as widely symbiotic, decreased in relative abundance. The response of Chlamydiae and Tenericutes, two phyla of mostly pathogenic species, decreased and increased along the precipitation gradient, respectively. Soil enzyme activity consistently increased under drought, a response that was attributed to drought‐induced changes in microbial community structure rather than to changes in abundance and diversity. Our results provide evidence that drought has a widespread effect on the assembly of microbial communities, one of the major drivers of soil function in terrestrial ecosystems. Such responses may have important implications for the provision of key ecosystem services, including nutrient cycling, and may result in the weakening of plant–microbial interactions and a greater incidence of certain soil‐borne diseases.

Apparent limitations in the ability of CMIP5 climate models to simulate recent multi-decadal change in surface temperature: implications for global temperature projections - Scott Power; François Delage; Guomin Wang; Ian Smith; Greg Kociuba (Climate Dynamics, 2017)

Ecology under lake ice - Stephanie E. Hampton; Aaron W. E. Galloway; Stephen M. Powers; Ted Ozersky; Kara H. Woo; Ryan D. Batt; Stephanie G. Labou; Catherine M. O'Reilly; Sapna Sharma; Noah R. Lottig; Emily H. Stanley; Rebecca L. North; et al. (Ecology Letters, 2017)
Winter conditions are rapidly changing in temperate ecosystems, particularly for those that experience periods of snow and ice cover. Relatively little is known of winter ecology in these systems, due to a historical research focus on summer ‘growing seasons’. We executed the first global quantitative synthesis on under‐ice lake ecology, including 36 abiotic and biotic variables from 42 research groups and 101 lakes, examining seasonal differences and connections as well as how seasonal differences vary with geophysical factors. Plankton were more abundant under ice than expected; mean winter values were 43.2% of summer values for chlorophyll a , 15.8% of summer phytoplankton biovolume and 25.3% of summer zooplankton density. Dissolved nitrogen concentrations were typically higher during winter, and these differences were exaggerated in smaller lakes. Lake size also influenced winter‐summer patterns for dissolved organic carbon ( DOC ), with higher winter DOC in smaller lakes. At coarse levels of taxonomic aggregation, phytoplankton and zooplankton community composition showed few systematic differences between seasons, although literature suggests that seasonal differences are frequently lake‐specific, species‐specific, or occur at the level of functional group. Within the subset of lakes that had longer time series, winter influenced the subsequent summer for some nutrient variables and zooplankton biomass.

Modelled impact of global warming on ENSO-driven precipitation changes in the tropical Pacific - Christine T. Y. Chung; Scott B. Power (Climate Dynamics, 2016)

The 10th Antarctic meteorological observation, modeling, and forecasting workshop - Steve R. Colwell; Arthur M. Cayette; Matthew A. Lazzara; Jordan G. Powers; David H. Bromwich; John J. Cassano; Scott Carpentier (Advances in Atmospheric Sciences, 2016)

Unambiguous warming in the western tropical Pacific primarily caused by anthropogenic forcing - Guomin Wang; Scott B. Power; Simon McGree (International Journal of Climatology, 2016)
Small Island Developing States in the tropical western Pacific are among the most vulnerable to climate change. While a great deal of information on the observed climate change trends and their cause is available for many other regions and for the globe as a whole, much less information has been available specifically for the Pacific. Here, we show that warming over the past 50 years in the western Pacific is evident in recently homogenized tropical station data, and in gridded surface temperature data sets for the region. The warming has already emerged from the background climate variability. The observational data and Coupled Model Intercomparison Project Phase 5 climate model output are used to show that the observed warming was primarily caused by human‐forced changes to the earth's radiative balance. Further warming is projected to occur in the same models under all three Representative Concentration Pathways ( RCPs ) considered ( RCP2.6 , RCP4.5 and RCP8.5 ), with the magnitude far exceeding the warming to date under the two scenarios with higher emissions ( RCP4.5 and RCP8.5 ).

A Tripole Index for the Interdecadal Pacific Oscillation - Benjamin J. Henley; Joelle Gergis; David J. Karoly; Scott Power; John Kennedy; Chris K. Folland (Climate Dynamics, 2015)

Precipitation response to La Niña and global warming in the Indo-Pacific - Christine T. Y. Chung; Scott B. Power (Climate Dynamics, 2014)

The eastward shift of the Walker Circulation in response to global warming and its relationship to ENSO variability - Tobias Bayr; Dietmar Dommenget; Thomas Martin; Scott B. Power (Climate Dynamics, 2014)

A new index for variations in the position of the South Pacific convergence zone 1910/11–2011/2012 - M. J. Salinger; Simon McGree; Florent Beucher; Scott B. Power; François Delage (Climate Dynamics, 2014)

Nonlinear precipitation response to El Niño and global warming in the Indo-Pacific - Christine T. Y. Chung; Scott B. Power; Julie M. Arblaster; Harun A. Rashid; Gregory L. Roff (Climate Dynamics, 2014)

Effects of an exercise and hypocaloric healthy eating program on biomarkers associated with long-term prognosis after early-stage breast cancer: a randomized controlled trial - E. Scott; A. J. Daley; H. Doll; N. Woodroofe; R. E. Coleman; N. Mutrie; H. Crank; H. J. Powers; J. M. Saxton (Cancer Causes & Control, 2013)

The impact of global warming on the Southern Oscillation Index - Scott B. Power; Greg Kociuba (Climate Dynamics, 2011)

Variability and decline in the number of severe tropical cyclones making land-fall over eastern Australia since the late nineteenth century - Jeff Callaghan; Scott B. Power (Climate Dynamics, 2011)

Simple analytic solutions of the linear delayed-action oscillator equation relevant to ENSO theory - Scott B. Power (Theoretical and Applied Climatology, 2011)

Atmospheric radiative feedbacks associated with transient climate change and climate variability - Robert A. Colman; Scott B. Power (Climate Dynamics, 2010)

A further analysis of the spatio‐temporal variability in aerosols across North America: Incorporation of lower tropospheric (850‐hPa) flow - Scott C. Sheridan; Helen C. Power; Jason C. Senkbeil (International Journal of Climatology, 2008)
In our previous research (Power et al. , 2006), we analysed the variability in spectral aerosol optical depth (τ a ), as well as Ångström's wavelength exponent (α), which represents the relative size distribution of aerosols, at 27 sites across North America. The variability was assessed by incorporating the Spatial Synoptic Classification (SSC) surface weather type across each of these sites. In this research, we further our analysis by examining the effect of different 850‐hPa flow patterns within the lower troposphere on variability in τ a and α. To accomplish this, an 850‐hPa flow classification was first developed from principal components analysis (PCA) and cluster analysis on National Centers for Environmental Prediction (NCEP)/The National Center for Atmospheric Research (NCAR) reanalysis geopotential‐height data, normalized by month of year. Nine flow types were identified. Cluster analyses yielded five clusters for both τ a and α. For τ a , spatially cohesive regions were identified, with a western cluster with low aerosol optical depth and minimal synoptic variability, and eastern clusters that showed higher turbidity as well as synoptic variability. In these clusters, higher turbidity was associated with southerly advection. For α, results were less cohesive, with clusters largely representing the different seasonal patterns of the variable, with synoptic variability difficult to interpret. Jackknifing was also utilized to evaluate whether τ a and α could be predicted based on SSC weather type and 850‐hPa flow type. Results varied at the three stations evaluated, with the method yielding potentially useful results for τ a across the two eastern sites, where synoptic variability at the surface and 850‐hPa is greater. At the western site, τ a could not be successfully predicted. Synoptic variability is too weak for α to be predicted effectively at any of the sites examined. Copyright © 2007 Royal Meteorological Society

Basic skills for working with smokers: A pilot test of an online course for medical students - Mary jo White; Beth M. Ewy; Judith Ockene; Scott Mcintosh; Jane Zapka; Catherine A. Powers; Alan Geller (Journal of Cancer Education, 2007)

Synoptic climatological influences on the spatial and temporal variability of aerosols over North America - Helen C. Power; Scott C. Sheridan; Jason C. Senkbeil (International Journal of Climatology, 2006)
The spatial and temporal variability of atmospheric aerosols is not well understood, as most studies have been constrained to data sets that include few stations and are of short duration. Furthermore, all methods for quantifying atmospheric turbidity suffer from a major constraint in that they require cloudless sky conditions. This restriction produces gaps in the turbidity record and sampling bias, which has led to questionable inferences about the variability of aerosols. In this research, we address these concerns via analyses at scales broader than all previous studies. We analyzed the spectral aerosol optical depth at 500 nm (τ a5 ) and Ångström's wavelength exponent (α), which represents the relative size distribution of aerosols. A total of 27 sites, with a mean period of record of 7.3 years, are included. Beyond seasonal and spatial summaries of aerosol variability, we have divided observations by synoptic condition, utilizing the Spatial Synoptic Classification (SSC). Our results show that atmospheric turbidity across North America is greatest over the east. Seasonality of both parameters was shown, most notably a greater τ a5 during summertime. Utilizing the SSC, we have uncovered significant differences across weather types. Moist weather types, especially moist tropical, display considerably higher turbidity, while the colder, drier dry polar weather type is associated with low aerosol optical depth. Certain weather types show considerable seasonal variability; the dry tropical weather type is associated with relatively low values in winter, but high values in summer, when convection is significant. Cluster analyses of stations yielded three general regions, each with similar synoptic variability: a western cluster with low aerosol optical depth and minimal synoptic variability, an eastern cluster with higher turbidity and variability, and a cluster located on the periphery of the eastern cluster, associated with moderate levels of turbidity but very high variability, suggesting a varied influence of nearby industrial areas. Copyright © 2006 Royal Meteorological Society.

Multi-year predictability in a coupled general circulation model - Scott Power; Rob Colman (Climate Dynamics, 2006)

Effects of vitamin E deficiency on fatigue and muscle contractile properties - Jeff Coombes; Benjamin Rowell; Stephen Dodd; Haydar Demirel; Hisashi Naito; Andrew Shanely; Scott Powers (European Journal of Applied Physiology, 2002)

Cloning and expression of an endocellulase gene from a novel streptomycete isolated from an East African soda lake - Pieter Solingen; Daan Meijer; Wilhelmus Kleij; Christopher Barnett; Robertus Bolle; Scott Power; Brian Jones (Extremophiles, 2001)

Decadal climate variability in Australia during the twentieth century - Scott Power; Faina Tseitkin; Vikram Mehta; Beth Lavery; Simon Torok; Neil Holbrook (International Journal of Climatology, 1999)

Decadal climate variability in Australia during the twentieth century - Scott Power; Faina Tseitkin; Vikram Mehta; Beth Lavery; Simon Torok; Neil Holbrook (International Journal of Climatology, 1999)

Exercise training protects against contraction-induced lipid peroxidation in the diaphragm - Heather K. Vincent; Scott K. Powers; Haydar A. Demirel; Jeff S. Coombes; Hisashi Naito (European Journal of Applied Physiology, 1999)

Seasonal migrations and reproductive patterns in the lake sturgeon, Acipenser fulvescens, in the vicinity of hydroelectric stations in northern Ontario - Scott McKinley; Glen Van Der Kraak; Geoff Power (Environmental Biology of Fishes, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)